What do energy modellers know? An ethnography of epistemic values and knowledge models. (August 2020) - Silvast, Antti; Laes, Erik; Abram, Simone; Bombaerts, Gunter
Abstract: This article considers academic energy modelling as a scientific practice. While models and modelling have been of considerable interest in energy social science research, few studies have brought together approaches from philosophy of science and anthropology to examine energy models both conceptually and in the applied sense. We develop a conceptual approach on epistemological ethics that distinguishes between epistemic values – such as accuracy, simplicity, and adequate representation – and non-epistemic values – such as policy relevance, methodological limitations, and learning – built into energy models. The research question is: how do modellers articulate and negotiate epistemic values and what does this imply for the status of models in scientific practice and policymaking? The empirical part of the article draws from ethnographic fieldwork and interviews amongst 40 energy modellers in university research groups in the UK from two complementary arenas: scholars preparing their PhD in modelling and scholars working in a large-scale energy modelling project. Our research uses ethnographic methods to complement themes recognised in earlier literatures on modelling, demonstrating what models and modellers know about the energy system and how they come to know it in particular ways.